Complete Genome Sequence of Iris Severe Mosaic Virus Isolated in Japan - Nishikawa, Masanobu (Microbiol Resour Announc, 2019)
The complete genome sequence of an iris severe mosaic virus isolate (ISMV) from Iris tectorum in Japan was determined for the first time. According to sequence identity analyses, our specimen is closely related to isolates reported from China.